2018
DOI: 10.1073/pnas.1718834115
|View full text |Cite
|
Sign up to set email alerts
|

Steroid signaling mediates nutritional regulation of juvenile body growth via IGF-binding protein in Drosophila

Abstract: Nutritional condition during the juvenile growth period considerably affects final adult size. The insulin/insulin-like growth factor signaling (IIS)/target of rapamycin (TOR) nutrient-sensing pathway is known to regulate growth and metabolism in response to nutritional conditions. However, there is limited information on how endocrine pathways communicate nutritional information to different metabolic organs to regulate organismal growth. Here, we show that Imaginal morphogenesis protein-Late 2 (Imp-L2), a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…The relationship between ecdysone and insulin signaling has been well elucidated in Drosophila , where ecdysone synthesis by the prothoracic gland is positively regulated by insulin‐signaling via FoxO (Koyama, Rodrigues, Athanasiadis, Shingleton, & Mirth, ), while ecdysone‐signaling in the fat body remotely suppresses the release of insulin‐like peptides from neurosecretory cells of the brain (Colombani et al, ). The activity of circulating insulin is further suppressed by the ecdysone‐regulated synthesis of insulin‐binding proteins impl2 (Honegger et al, ; Lee et al, ), which we found is at significantly higher levels in putatively wingless versus winged aphid embryos (Figure ). Thus, it is possible that the observed suppression of insulin‐signaling in embryos destined to be wingless is a consequence of elevated ecdysone signaling through maternally provided ecdysone (hypothesized relationship illustrated in Figure ).…”
Section: Discussionsupporting
confidence: 53%
“…The relationship between ecdysone and insulin signaling has been well elucidated in Drosophila , where ecdysone synthesis by the prothoracic gland is positively regulated by insulin‐signaling via FoxO (Koyama, Rodrigues, Athanasiadis, Shingleton, & Mirth, ), while ecdysone‐signaling in the fat body remotely suppresses the release of insulin‐like peptides from neurosecretory cells of the brain (Colombani et al, ). The activity of circulating insulin is further suppressed by the ecdysone‐regulated synthesis of insulin‐binding proteins impl2 (Honegger et al, ; Lee et al, ), which we found is at significantly higher levels in putatively wingless versus winged aphid embryos (Figure ). Thus, it is possible that the observed suppression of insulin‐signaling in embryos destined to be wingless is a consequence of elevated ecdysone signaling through maternally provided ecdysone (hypothesized relationship illustrated in Figure ).…”
Section: Discussionsupporting
confidence: 53%
“…Both energy resources acquired for juvenile growth and the timing of feeding cessation during the final larval instar are critical to the final adult body-size determination (36,37). Thus, we used the fifth-day fourth-instar larva when it stops feeding (wandering stage) as a checkpoint to determine the larval body size.…”
Section: Discussionmentioning
confidence: 99%
“…This increased circulating ecdysone level activates EcR in the fat body and upregulates the production of the IGF-binding partner (IGF-BP) ImpL2. Consequently, Imp-L2 binds to and inactivates the circulating DILPs attenuating peripheral IIS and body growth [52]. Third, by repressing miRNA mir8, the rise of ecdysone titers upregulates the mir8 target U-shaped which is a negative regulator of insulin signaling [53].…”
Section: Feedback Mechanisms Between Maturation and Growth Hormonesmentioning
confidence: 99%